2019
DOI: 10.17358/jabm.5.2.332
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kapitalisasi Pasar Saham dan Variabel Makroekonomi terhadap Indeks Harga Saham Gabungan di Bursa Efek Indonesia

Abstract: this research aimed to analyze the impact of stock market capitalization and macroeconomic variables on indonesia Composite index (iCi) and formulate recommendations of strategies to enhance stock market capitalization. the analysis of macroeconomic data variables covered the inflation rate, oil price, gold price, and Hang Seng Index from 2008 to 2017. the model used in this research was error Correction Model (eCM) and analytical hierarchy process (ahp). the results showed that in general, all independent var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 5 publications
1
8
0
8
Order By: Relevance
“…ROA, ROE, EPS, WCTO, gold price, oil price, Fed rate, systematic risk and government policy on FCX stock prices can be seen in Prob(F-statistic) 0.000000 Information: ***) Significant at the 1% level; **) Significant at the 5% level; *) significant at the 10% level interest rates, world oil prices and gold prices had an effect on the IDX. And (Hidayat, Firdaus and Sanim, 2019) disclose the significant positive effect of gold prices on the IDX.…”
Section: Long Run Affecting Factors Estimatementioning
confidence: 94%
See 3 more Smart Citations
“…ROA, ROE, EPS, WCTO, gold price, oil price, Fed rate, systematic risk and government policy on FCX stock prices can be seen in Prob(F-statistic) 0.000000 Information: ***) Significant at the 1% level; **) Significant at the 5% level; *) significant at the 10% level interest rates, world oil prices and gold prices had an effect on the IDX. And (Hidayat, Firdaus and Sanim, 2019) disclose the significant positive effect of gold prices on the IDX.…”
Section: Long Run Affecting Factors Estimatementioning
confidence: 94%
“…The results of this study are in line with (Suharno and Indarti, 2014) who revealed that the Indonesian bank interest rate, world oil prices and gold prices influence the IDX. And (Hidayat, Firdaus and Sanim, 2019) disclose the significant positive effect of gold prices on the IDX. disequilibrium was corrected in the current period by 67%.…”
Section: The Influence Of External Factorsmentioning
confidence: 94%
See 2 more Smart Citations
“…Pertumbuhan IHSG memberikan pengaruh yang positif terhadap nilai kapitalisasi pasar. Nilai ini merupakan perkalian dari total jumlah saham beredar dengan harga dari tiap saham (Hidayat et al 2019) dan saham-saham yang memiliki nilai kapitalisasi pasar tinggi merupakan saham-saham berkinerja baik yang memiliki volume penjualan saham dan harga saham yang tinggi sehingga akan mendorong nilai kapitalisasi sektor maupun indeks secara keseluruhan. Nilai kapitalisasi pasar terhadap sektor-sektor yang berada di dalam IHSG selama periode 2015-2018 ditunjukkan oleh Gambar 3 (OJK 2015(OJK , 2016(OJK , 2017(OJK , 2018 Keterangan: E(R i ) (expected return aset i); R it (return aset i dari periode t); n (jumlah periode penelitian); t (periode).…”
Section: Pendahuluanunclassified